Key competencies for digital transformation in workplace - Faina, I.; Almeida, F. (GFIC 2019: Proceedings of the 2nd Global Forum of Intellectual Capital, 2019)
While automation and artificial intelligence will eliminate very few jobs and occupations during the next decades, they will certainly affect and be present in portions of almost all jobs, either in a greater or lesser degree. Considering this fact, this research intends to identify which competencies are more valuable for workers who work in a technological workplace, by the perspective of the employers. It means this research will explore, listening employers opinion, which competencies are the ones that makes a worker leads and responds positively to a technological implementation in their workplace. Results were gathered through a Delphi study, within a panel of six experts in the human resources for technological industries field. It is finding that employers consider adaptability and creativity as the most important competencies for technological work. Notwithstanding, informatic competencies were less valuable by employers while considering the importance of these competencies for workers dealing with technology or robotic presence in workplaces.